Assessment of tannery effluents quality treated by electrocoagulation and ozonation: Physicochemical and ecotoxicological characterization - Edwar Aguilar-Ascón; Liliana Marrufo-Saldaña; Julio Barra-Hinojosa; Robert Buleje-del-Carpio (PLoS ONE, 2025)
Tannery effluents are characterized by their high toxicity and complex pollutant load, posing significant risks to aquatic ecosystems. Although conventional treatment processes often achieve regulatory standards for pollutant concentrations, they do not necessarily guarantee the reduction of effluent toxicity. This study aimed to evaluate the quality of tannery effluents treated by electrocoagulation (EC) and the combined electrocoagulation-ozonation (ECO) process, while analyzing the associated toxicity reduction, in order to determine the suitability of these technologies for application and ensure environmental protection of receiving water bodies. For this purpose, tannery wastewater was treated sequentially using an electrocoagulation reactor followed by an ozonation system, yielding three sample types: raw (C), electrocoagulation-treated (EC), and electrocoagulation-ozonation treated (ECO). Physicochemical parameters were measured, toxicity was assessed through bioassays with Lactuca sativa and Eisenia fetida, and chemical changes were analyzed using FTIR spectroscopy.EC achieved 96.4% removal of total suspended solids (TSS), 30.9% of chemical oxygen demand (COD), and 99% of chromium, while ozonation further removed 10% of COD and 99% of sulfides. Toxicity assays indicated a reduction from 23.89 toxicity units (TUs) in the raw effluent to 8.32 TUs after EC and 11.12 TUs after ECO. The slight increase in toxicity after ozonation was associated with elevated ammoniacal nitrogen levels and the formation of new functional groups, as evidenced by the FTIR spectrum. Despite significant pollutant removal, the results highlight that treated effluents may still present residual toxicity, emphasizing the need for complementary treatment strategies to achieve true environmental safety.